Effect of tear substitutes with various sodium hyaluronate levels on the condition of eye anterior segment in dry eye syndrome patients (Ukrainian Journal of Ophthalmology, 2026)
The purpose of the present paper was to compare the effect of tear substitutes with various sodium hyaluronate levels (0.21% and 0.4%) on eye anterior segment condition and to determine the informative value of various diagnostic tests in dry eye syndrome patientsMaterials and methods We followed up 40 patients (80 eyes), aged (57.8±7.5SD), with moderate dry eye syndrome (DES). All the patients were divided into two groups: group I included 20 patients (40 eyes) receiving 0.21% Optinol eye drops; group II included 20 patients (40 eyes) receiving 0.4% Optinol eye drops. Ophthalmic examination included Ocular Surface Disease Index (OSDI), biomicroscopy of the anterior chamber, fluorescence microscopy, tear break-up time for determining tear film stability, Schirmer’s I test and Jones' Schirmer II test to measure total and basal tear production, respectively; and best corrected visual acuity measurement.Results The use of hyaluronic acid-based tear substitute, 0.21% and 0.4% Optinol, showed good therapeutic efficacy and drug tolerability. The use of 0.21% and 0.4% Optinol eye drops significantly increased subjective complaints of DES patients, which is evidenced by an OSDI index. For diagnostics of  condition of the anterior eye segment in DES, it is most appropriate to use Schirmer II test, TBUT and LWE assessment which are most sensitive both in DES diagnostics and assessment of treatment quality. Since the 0.4% Optinol eye drops have a more pronounced moistening, anti-inflammatory, and protective action, it is reasonable to use them in the treatment of dry eye syndrome which is accompanied with apparent ocular surface tissue inflammation.
Keywords: dry eye syndrome; 0.21% and 0.4% sodium hyaluronate